Globalisation, indigenous tourism, and the politics of place in Amaicha (NW Argentine Andes) - Rainer, Gerhard (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
Argentina is a country that has represented itself over centuries as white and European. Over the last decades, however, indigenous movements have increased strongly in visibility and importance. This investigation considers this background in analysing the complex relationship between the growing importance of tourism and indigenous politics for self-determination and autonomy in the Andean village of Amaicha (NW-Argentina). The annual Pachamama celebration held by the indigenous Amaicha community presents the ideal setting for this research as it has simultaneously become a ‘national tourist festivity’ in the context of recent government efforts to promote a culturally diverse Argentina for tourism development. Through long-term ethnographic field work and by applying a methodological framework that combines the interpretation of visual material with careful empirical research this study presents a differentiated analysis of the political implications of indigenous tourism. The findings show that conflicts between the indigenous community and governmental institutions tend not to be about tourism and place promotion as such, but rather tourism has become a central arena where struggles over political control are manifested and mediated. Furthermore, cultural politics in Amaicha have recently been reassembled through both embodied practices and the use of cultural symbols during the Pachamama festivity. Finally, while relational conceptualisations of place as constituted through wider connections have gained momentum in academia, the results from this investigation show that an essentialised understanding of culture and identity as rooted in place is promoted for tourism, and emphasised by the indigenous community in order to legitimise claims for territorial and political rights. The goal of the paper is thus to contribute to a nuanced picture of emergent indigenous geographies in Argentina.